UPAYA UNITED NATION CHILDREN'S FUND (UNICEF) DALAM MENGATASI KRISIS AIR BERSIH DI INDIA PERIODE 2017-2020 - Andi Aliyah Weleidah Tenriawaru Patoppoi (2022)
The water crisis in India is expected to worsen given the population growth occurring in India. The existence of a water crisis poses a threat to Indian society, especially children. To overcome the water crisis, the Government of India has issued several programs, but these programs have not been able to completely overcome the problem of the water crisis. Thus, UNICEF, which operates with a mandate for the welfare of children around the world, has intervened to address the problems that threaten the lives of these children. This study aims to analyze and study the efforts made by UNICEF in overcoming the clean water crisis in India for the 2017-2020 period. The approach to the research carried out is a qualitative approach, with the type of descriptive-analytical research. The data sources used are primary and secondary data sourced from various literatures such as books, news, reports, as well as data discussing programs to overcome the clean water crisis issued by UNICEF and the Government of India. The data will then be analyzed using the Inter-Governmental Organization Concept and the Water Security Concept. Based on the data analysis conducted, it is concluded that the efforts made by UNICEF in overcoming the clean water crisis in India are through the Water, Sanitation, and Hygiene (WASH) Program and in collaboration with the Indian government through the National Rural Drinking Water Program and the Swajal Mission.